(untitled) (Jurnal Adabiya, 2024)
Libraries are the keeper of knowledge so libraries have the role to give their patrons knowledge that they need and that includes physical resources and online resources. This study sought to discover which resource researchers use in their research projects. The researchers gathered quantitative data from several bound theses throughout a five-year period from the library and all faculties of the school. Seven participants were interviewed to supplement the quantitative data. The quantitative results of the data analysis showed that there was a considerable difference in the utilization of resources throughout five years. The qualitative findings found that participants were mostly unaware about the services in the library thus it was hard for them to find relevant information in the library and relied mostly on online resources. The study concluded that online references were indeed the most used resources in research by undergraduate students. The study recommended that the library may need to advocate on activities that may increase library literacy on services like the Online Public Access Catalog (OPAC). ———————————————————————————————— Perpustakaan merupakan lembaga yang menjaga ilmu pengetahuan, kehadiran perpustakaan memiliki peran untuk memberikan pengetahuan yang dibutuhkan oleh pengunjungnya, termasuk sumber daya barbarslot fisik dan sumber daya daring. Penelitian ini bertujuan untuk menemukan sumber daya apa yang digunakan peneliti dalam proyek penelitian mereka. Para peneliti mengumpulkan data kuantitatif dari beberapa tesis terikat selama periode lima tahun dari perpustakaan dan semua fakultas di sekolah. Tujuh partisipan diwawancara untuk melengkapi data kuantitatif tersebut. Hasil analisis data kuantitatif menunjukkan adanya perbedaan yang cukup besar dalam pemanfaatan sumber daya selama lima tahun. Temuan kualitatif menunjukkan bahwa partisipan sebagian besar tidak menyadari layanan di perpustakaan sehingga sulit bagi mereka untuk menemukan informasi relevan di perpustakaan dan lebih mengandalkan sumber daya daring. Studi ini menyimpulkan bahwa referensi online memang menjadi sumber daya yang paling banyak digunakan dalam penelitian oleh mahasiswa sarjana. Studi ini merekomendasikan agar perpustakaan mungkin perlu mengadvokasi kegiatan yang dapat meningkatkan literasi perpustakaan pada layanan seperti Katalog Akses Publik Online (OPAC).